Cooperating in R&D and Advertising - Pourkarmi, Parisa; Atallah, Gamal (Université d'Ottawa | University of Ottawa, 2019)
This paper studies the impact of cooperative R&D and advertising on innovation and welfare in a duopolistic industry. The model incorporates two symmetric firms producing differentiated products. Firms invest in R&D and advertising in the presence of R&D spillovers and advertising spillovers. Advertising spillovers may be positive or negative. Four cooperative structures are studied: no cooperation, R&D cooperation, advertising cooperation, R&D and advertising cooperation. R&D spillovers and advertising spillovers always increase innovation and welfare if products are highly differentiated and/or spillovers are sufficiently high. The ranking of cooperation settings in terms of R&D, profits and welfare depends on product differentiation, R&D spillovers and advertising externalities. Firms always prefer cooperation on both dimensions, which is socially beneficial only when advertising and R&D spillovers are sufficiently high.
Keywords: R&D; advertising; cooperation; spillovers; product differentiation; innovation; marketing